Higher-order structure of barley chromosomes observed by electron tomography. (September 2022) - Hayashida, Misa; Sartsanga, Channarong; Phengchat, Rinyaporn; Malac, Marek; Harada, Ken; Akashi, Tetsuya; Fukui, Kiichi; Ohmido, Nobuko
Abstract: The higher order structure of the metaphase chromosome has been an enigma for over a century and several different models have been presented based on results obtained by a variety of techniques. Some disagreements in the results between methods have possibly arisen from artifacts caused during sample preparation such as staining and dehydration. Therefore, we treated barley chromosomes with ionic liquid to minimize the effects of dehydration. We also observed chromosomes on a film with holes to keep pristine chromosome structure from being flattened as seen when placed on a continuous support film. A chromosome placed over a hole in a thin carbon film was mounted on a tomography holder, and its structure was observed in three dimensions (3D) using electron tomography. We found that there are periodic structures with 300–400 nm pitch along the axis in barley chromosomes. The pitch sizes are larger than those observed in human chromosomes. Highlights: 3D structure of barley chromosomes was observed. The chromosomes were supported on a thin carbon film with holes. Longitudinally compressed stacks were observed. The pitch of the stacks was 300–400 nm.